PENGARUH PENGETAHUAN PEMERINTAH DAERAH TENTANG ANGGARAN, PARTISIPASI MASYARAKAT DAN TRANSPARANSI KEBIJAKAN PUBLIK TERHADAP PENYUSUNAN ANGGARAN DI KABUPATEN ENDE - Resi, Philipus Frederik; Reo, Hermanus; Banda, Falentina Lucia (Jurnal Riset Ilmu Akuntansi, 2020)
This study aims to determine the effect of knowledge of local government employees about budgets, knowledge of local government employees about community participation and knowledge of local government employees about transparency of public policies on budget preparation of the Regional Government of Ende Regency. The population in this study were employees of the Regional Development Planning Agency (BAPPEDA) and the Regional Financial and Asset Management Agency (SKPD) as budget compilers. The number of samples in this study amounted to 42 people. The sampling technique was carried out by means of a census technique and data was collected by distributing questionnaires to BAPEDA employees and the Regional Financial and Asset Management Agency. The data before being analyzed has been tested for validity and reliability. Then the analysis was carried out using multiple linear regression analysis techniques with data processing using the SPSS 16 program. Based on the research results, it shows that the knowledge of local government employees about the budget has a significant effect on budget preparation. Local government officials' knowledge of public participation has no effect on budget preparation. Meanwhile, the knowledge of local government officials about the transparency of public policies has a significant effect on the budgeting of the Ende District Government.